Implementation of Character Development for Boarding School Students Based on the Book Al-Akhlāq Lil-Banīn at the Darul Azhar Modern Islamic Boarding School in Southeast Aceh - Abd. Latif; Syamsu Nahar; Azizah Hanum OK (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2026)
This study examines moral character education, based on the book Al-Akhlāq Lil-Banīn, at Darul Azhar Modern Islamic Boarding School, focusing on its pedagogical framework, day-to-day implementation, and the factors that shape its success. Using a qualitative approach with participatory observation, in-depth interviews, and document analysis, the research finds that the book presents an organized framework that integrates cognitive, affective, and conative dimensions within a hierarchy encompassing both vertical relationships (with God) and horizontal ones (with other people). Its simple language, concrete examples, and gradual scaffolding suit adolescent development and current work in moral psychology. On the ground, the program runs through three overlapping channels: formal instruction, institutional habituation, and social control. Role-playing and dormitory routines prove especially effective. The findings also expose real tensions. Habituation dominates, and critical reflection is limited, so character formation rests more on habit than on deeply held belief. Most students show external regulation: they behave morally because someone is watching, and their conduct shifts across contexts. The study therefore argues for stronger, more structured reflection, less reliance on external control, and strategies that help students carry their moral commitments into settings that the pesantren cannot supervise